The Complex Structure of the Bulge of M31 - Denis Leahy; Traian Craiciu; Joseph Postma (The Astrophysical Journal Supplement Series, 2023)
The bulge of M31 is of interest regarding the nature of galactic bulges and how their structure relates to bulge formation mechanisms and their subsequent evolution. With the UVIT instrument on AstroSat, we have observed the bulge of M31 in five far-ultraviolet (FUV) and near-ultraviolet (NUV) filters at 1″ spatial resolution. Models for the luminosity distribution of the bulge are constructed using the UVIT data and the galaxy image fitting algorithm GALFIT. We fit the bulge without the nuclear region with a Sérsic function for the five images and find Sérsic indices (≃2.1–2.5) similar to previous studies but smaller R _e values (≃0.5–0.6 kpc). When fitting the images including the nuclear region, a multicomponent model is used. We use an eight-component model for the FUV 148 nm image, which has the highest sensitivity. The other images (169–279 nm) are fit with four-component models. The dust lanes in the bulge region are recovered in the residual images, which have subtraction of the bright bulge light using the multicomponent models. The dust lanes show that M31's nuclear spiral is visible in absorption at NUV and FUV wavelengths. The bulge images show boxy contours in all five UVIT wave bands, which is confirmed by fitting using GALFIT. The Sérsic indices of ∼2.1–2.5 are intermediate between the expected values for a classical bulge and for a pseudobulge. The boxiness of the bulge provides further evidence that M31's bulge has contributions from a classical bulge and a pseudobulge.